Application of Ultraviolet (UV) Radiation and Fluorescence for DIC Measurements - Quality Improvement. (November 2022) - König, Kristian; Reis, Martin; Vielhaber, Michael; Jung, Anne
Highlights: Improvement of digital image correlation (DIC) quality by UV radiation Using UV radiation with luminescent background colors for speckle pattern Monitoring of DIC quality by gray scale histograms Highly improvement of DIC quality on complex 3D cellular materials Abstract: Digital image correlation (DIC) is a widely used method in materials science and experimental mechanics for full-field surface displacement or strain measurements. It is an optical method, which calculates displacement or strain fields from images taken during deformation of the test specimen and is able to achieve a sub-pixel accuracy in case of proper operation. However, the theoretical accuracy is strongly reduced by effects such as surface reflections or shadows resulting from a not ideal illumination or lighting system. This is especially the case for complex 3D structured specimen geometries such as for metal foams or other cellular materials. The present study investigates the usage of ultraviolet (UV) light illumination in combination with phosphorescent or fluorescent pigments used to apply the needed speckle pattern for high accuracy DIC. A method to optimise the lighting system in combination with the used background pigments is presented. Fluorescent pigments provide much better results than phosphorescent pigments. The application of UV lighting in combination with fluorescent background pigments strongly improves DIC accuracy not only for normal tensile specimens but also for complex 3D shaped metal foams by avoiding surface reflections and shadows.